2000
DOI: 10.1002/1529-0131(200006)43:6<1278::aid-anr10>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four new quantitative trait loci regulating arthritis severity and one new quantitative trait locus regulating autoantibody production in rats with collagen‐induced arthritis

Abstract: Objective. Collagen-induced arthritis (CIA) is a polygenic model of experimentally induced autoimmunity and chronic joint inflammation. This study maps genetic loci that regulate CIA susceptibility in DA/Bkl (DA) and BN/SsNHsd (BN) rats.Methods. Genome scans covering chromosomes 1-20 and interval mapping techniques using 159 simple sequence-length polymorphism markers were used to identify quantitative trait loci (QTLs) that regulate CIA in (DA ؋ BN)F 2 hybrids. Serum antibody titers to type II collagen were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 70 publications
3
55
0
Order By: Relevance
“…This arthritis-regulating locus overlaps with the previously reported Cia11 locus, which was identified in experiments using DA and BN rats (20). Other significant loci that regulate clinical arthritis have previously been reported, as follows: on chromosome 4, Cia3/Pia5 and Cia13/Pia7, on chromosome 6, Cia20/Pia3, and on chromosome 12, Cia12/Pia4 (Table 2 and Figure 1A).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This arthritis-regulating locus overlaps with the previously reported Cia11 locus, which was identified in experiments using DA and BN rats (20). Other significant loci that regulate clinical arthritis have previously been reported, as follows: on chromosome 4, Cia3/Pia5 and Cia13/Pia7, on chromosome 6, Cia20/Pia3, and on chromosome 12, Cia12/Pia4 (Table 2 and Figure 1A).…”
Section: Resultssupporting
confidence: 82%
“…With regard to CIA in rats, most linkage analyses have been performed in the setting of bovine CIIinduced arthritis and in strain combinations other than E3 with DA (19)(20)(21)(22)(23). Therefore, in order to make a reasonable comparison of the genetic inheritance of CIA and PIA in rats, we performed linkage analysis of CIA in the same strain combination and induced by the same collagen source that was used for the PIA studies.…”
mentioning
confidence: 99%
“…39 Pia4 also colocalises with other QTLs for autoimmune disease, for example, Eae5, Eau2 and Cia12. 26,40,41 In a region on mouse chromosome 5, which is homologous to Pia4, association has been reported to arthritis severity of Lyme disease. 42 These findings indicate that common susceptibility genes for several autoimmune diseases exist.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodent intercrosses identified several arthritis susceptibility, severity and chronicity loci (Table 1). 29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] The RA genome-wide family-based genetic studies were not designed or structured to address disease severity, histologic damage or the other arthritis-related phenotypes that can be studied in rodents. More recent cohorts have been incorporating severity and outcome parameters in their prospective data collection and will likely have a major role in RA severity genetic association studies.…”
Section: Inducible Modelsmentioning
confidence: 99%